Wireless multimedia communications - Wesel, Ellen Kayata; Khayata, Ellen ([S.l.] : Addison Wesley Longman, 1998)
This book is a comprehensive guide to understanding the design of wireless multimedia communication systems. It addresses in detail each of the key elements of a complete wireless multimedia system and defines their relationships to one another. The author has made significant contributions to the theory, design, standardization, and policies of several wireless multimedia systems. This book will help engineers, managers, and graduate students design future wireless multimedia communication systems.